Quantum Sensing with Extreme Light. Issue 6 (25th March 2022) - Kutas, Mirco; Haase, Björn Erik; Riexinger, Felix; Hennig, Joshua; Bickert, Patricia; Pfeiffer, Tobias; Bortz, Michael; Molter, Daniel; von Freymann, Georg
Abstract: Optical nonlinear conversion processes are ubiquitously applied to scientific as well as industrial tasks. In particular, nonlinear processes are employed to generate radiation in many frequency ranges. In plenty of these nonlinear processes, the generation of paired photons occurs — the so‐called signal and idler photons. Although this type of generation has undergone a tremendous development over the last decades, either the generated signal or the idler radiation has been used experimentally. In contrast, novel quantum‐based measurement principles enable the usage of both partners of the generated photon pairs based on their correlation. These measurement approaches have an enormous potential for future applications, as they allow to transfer information from one spectral range to another. In particular, spectral ranges where photon generation and detection is particularly challenging can benefit from this principle. Above all, these include the extreme frequency ranges, such as on the low‐frequency side the mid to far infrared or even the terahertz spectral range, but also on the high‐frequency side the ultraviolet or X‐ray spectral range. In this review article, theoretical and experimental developments based on correlated biphotons are described specifically for the extreme spectral regions. Abstract : Quantum sensing provides access to photon properties in spectral ranges classically hard to address. Extreme light – here defined as widely separated from the visible range – enables highly attractive applications. This manuscript recaps the progress of nonlinear interferometry and related concepts with special focus on spectral ranges with large wavelength separation.